The Impact of Strategic Intelligence In Decision Making Styles An Analytical research in the Construction& Housing ministry - الشيخلي, عبد الرزاق ابراهيم; عبيد, مهند عواد (Journal of Economics and Administrative Sciences, 2015)
This research aims to explore the impact of strategic  intelligence by his dimensions (Foresight , system thinking, vision, motivation and partnership) on decision making styles which represented by ( rational, intuitive, dependent, Spontaneous and  Avoidant style) for a sample of the administrative leaders in the center of  Reconstruction &Housing Ministry and Some its formations which are companies of (Sa'ad, Al Mansour, al Farouq, Assyria, al-Mu'tasim, al- Rasheed, and Public Authority for Housing).  So to achieve the  research objectives and to test hypotheses, it has been relying on data collection form questionnaire as an essential tool, as well as field visits and personal interviews, the questionnaire distributed to the research sample's (104) of the decision makers in the the mentioned organizations, the number of forms recovered and valid was (77 ) form. Its undergone of statistical analysis using the program (SPSS) based on a set of statistical tools selected for the study of the relationship, the impact, and the differences between the variables, like (arithmetic mean (Mean), standard deviation (Std), the coefficient of variation (C. V.), link simple linear (Pearson), simple linear regression (Simple Regression Coefficient.  The research found a set of results, most notably the presence significant of correlation and the effect between strategic intelligence at general level and subsidiary dimensions except partnership and between the decision-making styles , with the exception of avoided style , while not indicate those results are differences in the level of awareness of strategic intelligence and the decision-making style between the center of the ministry and its formations researched.Based on the findings of the research results it has developed a set of recommendations was the most important to make strategic intelligence part of the organizations surveyed culture by investing realize the managers of some of the details and work on disseminate in all parts of the organization, and to encourage the submission of creative ideas and creativity and that contribute to the investment Perceptions strategic intelligence leaders have in adopting effective decisions